What kind of teacher should we become: identity–role consistency and authenticity - Li, Hanqiang (Frontiers in Education, 2025)
In the field of teacher education identity conflict and role conflict frequently emerge. Conflict arises not only within the identity system or the role system but also between identity and role, manifesting as a misalignment between cognitive commitments and behavioral expectations. This phenomenon is termed cross conflict between identity and role. Through a systematic review of 117 high-quality Chinese and English studies the theoretical meanings of profession role and identity are clearly delineated and the concept of Identity-Role Consistency is advanced as a novel construct for assessing the significance and feasibility of internal professional conflict among teachers. Identity-Role Consistency denotes the degree of congruence between a teacher’s sense of professional identity and the expectations of their role and holds promise as a quantifiable indicator of teacher psychological well-being. The study further introduces self authenticity to emphasize individual traits and integrates it critically with Identity-Role Consistency.